Allah Tritunggal: Allah Yang Bersahabat - Kristoforus Bala (Seri Filsafat Teologi, 2020)
This article is to describe the imageof the Trinity God who is affectionate based on the Holy Bible and the Church Tradion. The Trinity is God who is Supreme good, plural as well as singular, all-Merciful, inclusive, communicative, and affectionate. God reveals Himself through His creations, the Israelities exodus, the commission of Jesus and the Holy Spirit. In the mids of the world that is easily segregated by the issues of ethnocentrism, radicalism, primodialism, religious fundalism, sacism, horizontal conflicts, etc; the image of the affectionate Trinity God could be the source of inspirations and model to the reformation and transformation of the human race’s better, friendly, harmonious, affectionate, inclusive, and humane life.